Programming Microsoft Visual C# 2005: The Language - Marshall, Donis (Microsoft Press, 2011)
Offering expert guidance, hands-on programming instruction, and practical examples, this straightforward book will help both new and experienced developers advance their proficiency in developing applications for Microsoft Windows and the Web.